Feeding habits of three seal species at the Danco Coast, Antarctica: A re-assessment - Casaux, Ricardo Jorge; Bertolin, María Lila; Carlini, A. (Polar Biology)
The analysis of prey overlap among Weddell, Antarctic fur and leopard seals was conducted using fecal samples collected at the Danco Coast, Antarctic Peninsula, in 1998 and 2000. The re-occurrence of prey species was moderate in samples collected in 1998, and low in 2000, and reflects resource partitioning among seal species. Prey species that mostly co-occurred in seals' diet were the Antarctic krill Euphausia superba, bivalves, and the myctophids Gymnoscopelus nicholsi and Electrona antarctica. A dietary similarity index of prey overlap has been calculated and demonstrates evident fluctuations in pairwise comparisons between the seal species. The highest and lowest values of prey overlap were observed between Antarctic fur seals and leopard seals, and between Weddell seals and leopard seals, respectively. Prey overlap between Antarctic fur seals and Weddell seals was moderate in both seasons. Fil: Casaux, Ricardo Jorge. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Bertolin, María Lila. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Carlini, A. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina